Efeito do etileno sobre o tipo e qualidade da bebida de café - Sondahl, Maro R.; Teixeira, Aldir A.; Fazuoli, Luiz C.; Monaco, Lourival C. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Previous studies have shown that Ethrel accelerated the process of maturation so that coffee fruits mature 15 days after application. In the present work the effect of 2-chloro ethane-phosphonic acid (Ethrel) applications on coffee berry maturation and cup quality is reported. Ethrel in concentrations of 0, 500, 1000 and 2000 ppm of active product was applied at two stages of fruit maturity. Samples of harvested fruits contained about 40 and 10 per cent of defective "greens" seeds (verdes), according with the official Brazilian Classification, for the first and second dates studied respectively. Evaluation concerning with cup quality, statistically significant differences were found between the time of application but not between the doses. The first application produced a high incidence of immature endosperm wich resulted in poor cup quality (Hard). Late treatment resulted in good cup quality (Mild). These observation suggest that Ethrel can be used in order to obtain more uniform maturation of the berries without affecting the quality of coffee as long as all the fruit are completely developed at the time of application